Indicadores fonorrespiratorios de normalidad y patología en la clínica vocal - Vila-Rovira, Josep Maria; Valero-Garcia, Jesus; Gonzalez-Sanvisens, Laura (Revista de Investigación en Logopedia, 2011)
Dysphonia is a disorder of the voice qualities. These qualities can be measured and these values may provide relevant information for clinical professionals of voice. This research aims to identify the most valid measures in the study of pathological voice and set cut-off values to identify the population hoarse. We have studied the voice of 141 people with vocal disorders and compared with a control group of 99 subjects. The results show significant differences in several parameters and values can shape cut-off in the maximum frequency (537 Hz - C4 in men and 667 Hz - Mi4 in women) and in the Dysphonia Severity Index (3.70). The diversity and variability observed of the data call to the clinician to integrate the data the objective measures with their qualitative perceptions, subjective assessments of the patient and the information obtained by the laryngeal images.